Transseptal Suturing Reduce Patient Anxiety after Septoplasty Compared to Nasal Packing - Sari, Kamran; Gul, Ali Irfan; Kantekin, Yunus; Karaaslan, Ozgul; Gencer, Zeliha Kapusuz (Acta medica (Hradec Kralove), 2016)
BACKGROUND: We measured postoperative anxiety in patients who underwent transseptal suturing or nasal packing after septoplasty. MATERIALS AND METHODS: Transseptal suturing was performed on Group 1 patients and nasal splints with airway were placed after septoplasty in Group 2 patients. Postoperative 48-h anxiety levels of both groups were measured using the State-Trait Anxiety Inventory (STAI) clinical assessment scale, prior to removal of nasal packing in Group 2. RESULTS: Transseptal suturing was performed after septoplasty in 28 patients and nasal packing in 34 patients. The State-Trait Anxiety Inventory clinical assessment state (STAI-S) and trait (STAI-T) instruments were used to measure postoperative anxiety. The STAI-S scores were found 35.00 in the transseptal suturing group and 43.8 in the nasal packing group; the difference was found significant (p < 0.05). The STAI-T scores were found 42.6 in the transseptal suturing group and 45.7 in the nasal packing group; the difference was not found significant (p > 0.05). The rate of minor hemorrhage was found 10.7% in Group 1 patients. CONCLUSIONS: Transseptal suturing is simple and reliable when performed after septoplasty. The technique is painless and comfortable, and reduces patient anxiety (compared to that associated with nasal packing) with only a minor increase in operating time and hemorrhage.
Keywords: Transseptal suturing; Humans; úzkost; nosní přepážka; hemostáza chirurgická; Nasal Septum; Postoperative Period; Female; mladý dospělý; dospělí; Septoplasty; Hemostasis, Surgical; lidé; rinoplastika; Anxiety; Adult; ženské pohlaví; Male; šicí techniky; Rhinoplasty; Cross-Sectional Studies; Young Adult; Aanxiety; Suture Techniques; mužské pohlaví; prospektivní studie; pooperační období; Nasal packing; průřezové studie; Prospective Studies